2020
DOI: 10.20886/jpth.2020.14.2.101-110
|View full text |Cite
|
Sign up to set email alerts
|

DETEKSI DAN IDENTIFIKASI Austropuccinia psidii PADA MYRTACEAE DI YOGYAKARTAINDONESIA

Abstract: Austropuccinia psidii is a pathogenic fungus that causes rust in the Myrtaceae plant. The extensive plantation of the host of this fungus has increased the attack of fungal pathogen, therefore, will increase the threat tothe presence of Myrtaceae species around the globe including in Indonesia. This present study was aiming to detect and identify the presence of this pathogen by morphologicaland molecular observation. Morphological observationrevealed the presence of A. psidii uredinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study indicates that M. cajuputi is one of the most susceptible hosts compared to S. polyanthum and S. myrtifolium. A study by Prihatini et al (2020) showed that diseased M. cajuputi comprises shoot death and severe infection on the branch and older leaves. Currently, there is no report on the economic loss caused by myrtle rust in Indonesia, but in New Zealand, this pathogen is predicted to cause real GDP to fall by between $144 million and $411 million relative to baseline by 2030 (NZIER 2017).…”
Section: Austropuccinia Psidii Symptoms On Myrtaceaementioning
confidence: 99%
See 1 more Smart Citation
“…This study indicates that M. cajuputi is one of the most susceptible hosts compared to S. polyanthum and S. myrtifolium. A study by Prihatini et al (2020) showed that diseased M. cajuputi comprises shoot death and severe infection on the branch and older leaves. Currently, there is no report on the economic loss caused by myrtle rust in Indonesia, but in New Zealand, this pathogen is predicted to cause real GDP to fall by between $144 million and $411 million relative to baseline by 2030 (NZIER 2017).…”
Section: Austropuccinia Psidii Symptoms On Myrtaceaementioning
confidence: 99%
“…This rust also threatens many native and endemic Myrtaceae species in Australia, such as Rhodamnia rubescens, Rhodomyrtus psidioides, Eucalyptus amplifolia, Kunzea parvifolia, Austromyrtus inophloia, and other 370 or more native plants (Winzer et al 2019). This rust has been reported to infect some Myrtaceae species in Indonesia, such as E. grandis x E. pellita, M. leucadendra in the north and south Sumatra (McTaggart et al 2016), as well as S. polyanthum, and M. cajuputi in Yogyakarta, Java (Prihatini et al 2020). Pegg et al (2017) stated that A. psidii infects young organs of plants, such as young flowers, fruits, and leaves.…”
Section: Introductionmentioning
confidence: 99%